Influence Mechanism of Social Support of Online Travel Platform on Customer Citizenship Behavior - Ning, Yu-mei; Hu, Chuan (Frontiers in Psychology, 2022)
Customer citizenship behavior has attracted widespread attention from scholars due to its capacity of enabling enterprises to gain competitive advantages of low costs and high efficiency by giving full play to the initiative of customers. Based on the S-O-R Model, we have established the theoretical model to study the influence imposed by social support of online travel platform enterprises on customer citizenship behavior against the backdrop of the sharing economy. This research tests the fitting of the theoretical model and its fundamental hypotheses using 626 samples acquired from the investigation with SPSS26.0 and AMOS25.0. Results indicate that the social support has a positive influence on customer citizenship behavior. Social support could have a positive influence on positive emotions. Social support has no significant negative effect on negative emotions. Positive emotions have a positive influence on customer citizenship behavior. Negative emotions have a negative influence on customer citizenship behavior. Positive emotions play a mediating effect in the positive influence of social support on customer citizenship behavior. Social support could have a positive influence on customer satisfaction. Customer satisfaction has a positive influence on customer citizenship behavior. Customer satisfaction plays a mediating effect in the positive effect of social support on customer citizenship behavior. Positive emotions and customer satisfaction play a chain mediating effect in the positive effect of social support on customer citizenship behavior.